Network analysis of frontal lobe alpha asymmetry confirms the neurophysiological basis of four subtypes of depressive behavior - Sharpley, Christopher F.; Bitsika, Vicki; Arnold, Wayne M.; Shadli, Shabah M.; Jesulola, Emmanuel; Agnew, Linda L. (Frontiers in Psychiatry, 2023)
Introduction: Although depression is widespread carries a major disease burden, current treatments remain non-universally effective, arguably due to the heterogeneity of depression, and leading to the consideration of depressive 'subtypes' or 'depressive behavior subtypes'.One such model of depressive behavior (DB) subtypes was investigated for its associations with frontal lobe asymmetry (FLA), using a different data analytic procedure than in previous research in this field.Methods: 100 community volunteers (54 males, 46 females) aged between 18yr and 75 years (M = 32.53yr, SD = 14.13yr) completed the Zung Self-rating Depression Scale (SDS) and underwent 15 min of eyes closed EEG resting data collection across 10 frontal lobe sites. DB subtypes were defined on the basis of previous research using the SDS, and alpha-wave (8-13Hz) data produced an index of FLA. Data were examined via network analysis.Results: Several network analyses were conducted, producing two models of the association between DB subtypes and FLA, confirming unique neurophysiological profiles for each of the four DB subtypes. Discussion: As well as providing a firm basis for using these DB subtypes in clinical settings, these findings provide a reasonable explanation for the inconsistency in previous FLAdepression research.